Progress on antimicrobial surgical gloves: A review - Arman Amani, B.; Bagheri, Samira; Hamid, Sharifah Bee Abd (2015)
Surgical gloves provide a protective blockade for patients and members of the surgical team. Glove integrity is critical in an era of blood-borne pathogens. Therefore, the need for improved means for prevention and also gloving and appropriate hand hygiene in a hospital setting is ostensible. This perspective highlights the progress on antimicrobial surgical gloves in deducting the microbial passage after a glove puncture in a model of wound contamination. Moreover, traditional methods to avoid microbes in the hospital and various antimicrobial agents, such as metal ions and antiseptic dyes, are reviewed.